(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
Repeated activation of muscle induces processes resulting in decreased performance (fatigue) as well as enhanced performance (postactivation potentiation, (PAP)). This implies that at any time during contraction, fatiguing effects are being countered by potentiation effects, and vise versa. Therefore, which of the processes will be prevalent during and after explosive strength training is not clear. The purpose of this investigation was to study the acute neuromuscular responses to one explosive strength training session. Eleven healthy untrained men (aged 22—35 years) performed explosive strength training session of six sets (ﬁ ve repetitions each) of the unilateral isometric contractions at an angle of 90 degrees in the knee. The contractility of the muscle was monitored via the electrically evoked contractions at 1, 20, and 50 Hz (P 1, P 20, and P 50, re- spectively) before (Ini), after the ﬁ rst and sixth sets as well as during the 5 and 30 min recovery period (A 5 and A 30, respectively). Contraction time (CT) and relaxation time (RT) of a single twitch (P1) of quadriceps was registered. Maximal voluntary contraction (MVC) force as well force developed during 100 ms (MVC 0-100ms ) was also determined. The ratio of P 20 / P 50 kinetics after exercise was used for the evaluation of low-frequency fatigue (LFF). There was statistically signiﬁ cant repetition effect observed on MVC (p = 0.045) and MVC 0-100ms (p = 0.012). After the ﬁ rst set there was a signiﬁ cant increase in muscle force induced by very low (1 Hz) and low (20 Hz) stimulation frequencies and did not change during all explosive strength training session (p < 0.05). The ratio of P 20 / P 50 recorded after the ﬁ rst set increased signiﬁ cantly (p < 0.05), however 30-min after the explosive strength training session it was signiﬁ cantly decrease in P 20 / P50 ratio compared to its Ini level (p < 0.05). The present study showed that potentia- tion increases P 20 / P 50 ratio during the explosive strength training session, however the subsequent (after 30 min of recovery) decline in P 20 / P 50 ratio is an outcome of diminishing inﬂ uence of potentiation on the background of persistent LFF. Therefore, when muscles are potentiated, it may seem as if no LFF is present. Keywords: explosive strength training, low-frequency fatigue, maximum voluntary contraction, post-activation potentiation.